2015
DOI: 10.1186/s13071-015-1113-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chemical constituents of Zanthoxylum heitzii stem bark and their insecticidal activity against the malaria mosquito Anopheles gambiae

Abstract: BackgroundZanthoxylum heitzii bark extracts have insecticidal properties and have been reported to be used against malaria in Western Africa. Previously, it has been shown that a hexane extract of the bark is toxic to adult females of the mosquito Anopheles gambiae, a malaria vector. As part of our project on the control of malaria vectors using plant extracts, the phytochemistry of Z. heitzii bark hexane extract has been investigated with the aim to identify the major components with adulticidal and larvicida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…The Larvicidal efficacy of ethanol extracts of D. erecta, T. procumbens and P. purpureum against A. gambiae fourth instar larvae revealed that all the tested plant extracts were active against the test organism, as pupation was inhibited in a considerable number of larvae. Similar studies on the larvicidal activities of plants belonging to different families have been reported by various authors against the A. gambiae larvae including Gnetum ula, Spermacoce hispida [57], Artemisia annua [62], Plumbago zeylanica, Plumbago dawei and Plumbago stenophylla [66], Persea Americana [67], Citrus reticulata, Citrus limon, Citrus aurantifolia, Citrus sinensis, Citrus paradise [10], Clausena anisate [11], Zanthoxylum heitzii [12], Lippia adoensis [13], ISSN: 2456-7132 Available online at Journals.aijr.in…”
Section: )supporting
confidence: 73%
See 1 more Smart Citation
“…The Larvicidal efficacy of ethanol extracts of D. erecta, T. procumbens and P. purpureum against A. gambiae fourth instar larvae revealed that all the tested plant extracts were active against the test organism, as pupation was inhibited in a considerable number of larvae. Similar studies on the larvicidal activities of plants belonging to different families have been reported by various authors against the A. gambiae larvae including Gnetum ula, Spermacoce hispida [57], Artemisia annua [62], Plumbago zeylanica, Plumbago dawei and Plumbago stenophylla [66], Persea Americana [67], Citrus reticulata, Citrus limon, Citrus aurantifolia, Citrus sinensis, Citrus paradise [10], Clausena anisate [11], Zanthoxylum heitzii [12], Lippia adoensis [13], ISSN: 2456-7132 Available online at Journals.aijr.in…”
Section: )supporting
confidence: 73%
“…It has been discovered that plants generally produce many secondary metabolites which constitute an important source of microbicides, pesticides and many pharmaceutical drugs [9]. Varieties of plants such as Citrus paradise [10], Clausena anisate [11], Zanthoxylum heitzii [12], Lippia adoensis [13], Chromolaena odorata [14], Ageratum conyzoides [15] with insecticidal activities have been reported. Duranta erecta (Linn), also known as golden dewdrop, pigeon berry, angel whisper, or sky flower in English, is a shrub usually 1 to 3 m in height.…”
Section: Ovicidal and Larvicidal Activities Of Ethanolic Leaf Extractmentioning
confidence: 99%
“…The plant material was extracted and natural products isolated according to Moussavi et al [ 18 ] and Wangensteen et al [ 19 ]. Briefly, the stem bark, seeds and leaves were air dried and made into a powder (<1 mm).…”
Section: Methodsmentioning
confidence: 99%
“…The powdered plant materials were first extracted with hexane in a Soxhlet extractor until the effluent was colorless, and then subsequently extracted with ethyl acetate and ethanol in an accelerated solvent extractor, ASE350 (Dionex) [ 17 ]. The pure compounds were obtained from the bark hexane extract as previously described [ 18 , 19 ] by Si-gel normal phase and reverse phase C18 chromatography. The powdered bark (<1 mm), 10 g, was mixed with 100 g water and refluxed for 20 min to mimic a common way of preparing herbal drugs, making a decoction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation